PENGATURAN PAJAK KENDARAAN BERMOTOR DI KOTA KUPANG - Ngau Lobo, Ferdinandus; Hallan, Markus A.K.B; Putra Seran, Eusebius Samudra; Odjan, Theresia Denisa Saraswati; Moru, Rosalia; B.Cermeta, Amelia Leni; Haba, Apriyanto Huki; Hoar, Ayuni Adelbertha; Paskalis Maggi, Yahyadi Agung; Echa Kelen, Aurelia Agatha; et al. (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The Motor Vehicle Tax (PKB) is one of the important sources of revenue for local governments in order to support development and strengthen fiscal independence. This study aims to analyze legal arrangements related to PKB in Kupang City and identify factors that affect the level of community compliance in paying the tax. The method used is a juridical-normative and empirical approach by examining the applicable laws and regulations and implementation data in the field. The results of the study show that the PKB regulation in Kupang City is in accordance with national provisions such as Law Number 28 of 2009 and Law Number 1 of 2022, and is strengthened by Kupang City Regional Regulation Number 1 of 2024 which regulates the collection of PKB and BBNKB options. Although legal tools have been available, the level of public compliance is still low due to various factors, including low legal understanding, negative perception of tax rates, less effective administrative sanctions, and suboptimal public services. For this reason, it is necessary to increase legal socialization, evaluate the implementation of regional regulations, and improve the quality of services to support the effectiveness of tax policies at the regional level.